2006
DOI: 10.1177/0892705706067480
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic–Mechanical Properties of Wood–Fiber Reinforced Polylactide: Experimental Characterization and Micromechanical Modeling

Abstract: Wood-fiber reinforced polylactide is a biodegradable composite where both fibers and matrix are from renewable resources. When designing new materials of this kind, it is useful to measure the influence of fiber-matrix interface properties on macroscopic mechanical properties.In particular, a quantitative measure of the dynamic stress transfer between the fibers and the matrix when the material is subjected to cyclic loading would simplify the development of wood-fiber composites. This is obtained by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Thermal properties of samples were evaluated by differential scanning calorimetry (DSC) performed on DSC7 [15][16][17][18][19][20] Cellulose fibers [21][22][23] Cellulose whiskers [24] Microcrystalline cellulose [21,25] Wood flour and fibers [21,26,27] Flax fibers [23,28,29] Hemp fibers [30,31] Kenaf fibers [32,33] Bamboo fibers [34] Jute [21,35] Corn husks and stover [36,37] Apple solids and fibers [38,39] Sugar beet pulp [38,40] Oat husks [39] Cocoa shells [39] Wheat straw [37] Soy stalks [37] Abaca leaves [41] Green coconut [42] Cuphea and lasquerella seeds [43] Cotton burr and hull [44] Polyethylene Starch [45][46][47][48][49][50][51][52]…”
Section: Characterizationmentioning
confidence: 99%
“…Thermal properties of samples were evaluated by differential scanning calorimetry (DSC) performed on DSC7 [15][16][17][18][19][20] Cellulose fibers [21][22][23] Cellulose whiskers [24] Microcrystalline cellulose [21,25] Wood flour and fibers [21,26,27] Flax fibers [23,28,29] Hemp fibers [30,31] Kenaf fibers [32,33] Bamboo fibers [34] Jute [21,35] Corn husks and stover [36,37] Apple solids and fibers [38,39] Sugar beet pulp [38,40] Oat husks [39] Cocoa shells [39] Wheat straw [37] Soy stalks [37] Abaca leaves [41] Green coconut [42] Cuphea and lasquerella seeds [43] Cotton burr and hull [44] Polyethylene Starch [45][46][47][48][49][50][51][52]…”
Section: Characterizationmentioning
confidence: 99%
“…The adhesion between the fibres and the matrix is crucial to all fibre composites. Provided good adhesion, the stress is transferred between the load carrying fibre and the matrix (Bogren et al, 2006), which increases the mechanical properties. Coupling agents can be used to improve the adhesion, both for traditional thermoplastics (e.g.…”
Section: Fibre-reinforced Compositesmentioning
confidence: 99%
“…They concluded that their method was convenient, but rather approximate. In previous work by Bogren et al [6], the effect of moisture on a wood-fiber/polylactide interface was studied. Halpin-Tsai's micromechanical model and laminate analogy was used to account for softening and swelling of the constituents and thereby isolate moist induced changes of the stress transfer ability of the interface.…”
Section: Introductionmentioning
confidence: 99%